PEMANFAATAN PUPUK KANDANG UNTUK BUDIDAYA Daphnia sp. SEBAGAI PAKAN ALAMI IKAN LELE (Clarias sp.) - Sari, Annisa Novita; Hidayati, Sri; Mujtahidah, Tholibah (JURNAL KASTARA, 2022)
One of the determining factors the success of aquaculture is the provision of fish feed. There are many types of fish feed sold in the market, ranging from natural feed to artificial feed. One type of natural fish feed was Daphnia sp. Growth of Daphnia sp can be maximized by utilizing livestock waste as an additional nutrient. The aim of this community partnership program was to socialize to the public about Daphnia sp natural food and provide training to the community on how to cultivate Daphnia sp. The main target was an aquaculture stakeholder namely Women Farmers Group of Permai Tani which was in Gandusari Village, Bandongan District, Magelang Regency. The stages of this activity include tools and materials preparation, program of socialization to partners, implementation, and evaluation program. The working steps of implementing the activity were preparing the tools and materials needed including Daphnia sp seeds, livestock waste (goat manure, chicken manure and eggs) and catfish cultured wastewater as a culture medium. This activity has been carried out well, socialization and training attended by participants from Women Farmers Group of Permai Tani members. The enthusiasm of the participants was very good. This can be seen from sharing and asking activity about how to cultivate Daphnia sp. The results of this activity can increase the production of Daphnia sp which was used as natural fish feed in Gandusari Village, Bandongan District, Magelang Regency.